Inside asset purchase programs: the effects of unconventional policy on banking competition - Michael Koetter; Natalia Podlich; Michael Wedow (European Central Bank (ECB), 2017)
We test if unconventional monetary policy instruments influence the competitive conduct of banks. Between q2:2010 and q1:2012, the ECB absorbed exteuro218 billion worth of government securities from five EMU countries under the Securities Markets Programme (SMP). Using detailed security holdings data at the bank level, we show that banks exposed to this unexpected (loose) policy shock mildly gained local loan and deposit market shares. Shifts in market shares are driven by banks that increased SMP security holdings during the lifetime of the program and that hold the largest relative SMP portfolio shares. Holding other securities from periphery countries that were not part of the SMP amplifies the positive market share responses. Monopolistic rents approximated by Lerner indices are lower for SMP banks, suggesting a role of the SMP to re-distribute market power differentially, but not necessarily banking profits.
Keywords: C30; C78; G21; G28; L51; 330; competition; security markets program; unconventional monetary policy